SEGMENTASI DAN POLA PERILAKU PENGGUNA FACEBOOK (Studi pada mahasiswa Universitas Muhammadiyah Malang) - Imam Hariyadi (Universitas muhammadiyah malang, 2012)
Imam HariyadiUniversitas Muhamadiyah MalangE-mail: Iamhariyadi3@gmail.comABSTRACTThe purpose of this study was to determine the characteristics and behaviour patterns among facebookusers at Students University of Malang. This descriptive type of research used the sample of 100respondents. A non-probability sampling technique used judgmental sampling. The scale was based onthe Likert measurement and this analysis include: the validity and reliability. The analysis of the dataobtained used a variable frequency distribution analysis consisting of Demographic (gender, incomelevel), psychographic (activities, interests, opinions) and behaviour (benefits, attitudes). The results ofthe analysis of the distribution of the respondents classify based on the frequency of demographic,psychographic, and behaviour which they claim that face-book provides entertainment as an alternativeto in their spare time. Information obtained, such as the latest news both locally and internationally,information on lectures, job listings, buying and selling. They also interact or communicatewith the community group.Keywords: Frequency Distribution Analysis, Behaviour Patterns, Characteristics